2019
DOI: 10.1371/journal.pone.0219336
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of heavy metals in some commercially important fishes from a tropical river estuary suggests higher potential health risk in children than adults

Abstract: The Karnaphuli River estuary, located in southeast coast of Bangladesh, is largely exposed to heavy metal contamination as it receives a huge amount of untreated industrial effluents from the Chottagram City. This study aimed to assess the concentrations of five heavy metals (As, Pb, Cd, Cr and Cu) and their bioaccumulation status in six commercially important fishes, and also to evaluate the potential human health risk for local consumers. The hierarchy of the measured concentration level (mg/kg) of the metal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
78
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(102 citation statements)
references
References 87 publications
16
78
7
1
Order By: Relevance
“…Similar bioaccumulation of As, Cd, Pb, and Hg have been reported in P. fulvidraco , C. auratus , and H. nobilis collected from Nansi Lake of China 18 . In a recent study, accumulation of As, Pb, Cd, Cr, and Cu in six edible fish species was studied where Cd, Pb and Hg were suggested as highly deleterious heavy metals accompanied by Cu, Cr, Ni, Mn, and Zn and their high solubility produce threat to inhabiting fish 6 . Prolonged exposure to even very low amounts of heavy metals could lead to leakage of pathology marker enzymes, immunotoxicity, and genotoxicity in different tissues of fish 19 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar bioaccumulation of As, Cd, Pb, and Hg have been reported in P. fulvidraco , C. auratus , and H. nobilis collected from Nansi Lake of China 18 . In a recent study, accumulation of As, Pb, Cd, Cr, and Cu in six edible fish species was studied where Cd, Pb and Hg were suggested as highly deleterious heavy metals accompanied by Cu, Cr, Ni, Mn, and Zn and their high solubility produce threat to inhabiting fish 6 . Prolonged exposure to even very low amounts of heavy metals could lead to leakage of pathology marker enzymes, immunotoxicity, and genotoxicity in different tissues of fish 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Turan et al 5 took Clarias gariepinus as a bioindicator of Orontes River, Turkey to highlight the degraded quality of water and adverse effects of heavy metals (Cr, Cd, Cu, Fe and Mn) in terms of bioaccumulation, oxidative stress and genotoxicity. Ahmed et al 6 studied the bioaccumulation of heavy metals (As, Pb, Cd, Cr and Cu) in different species of fish Apocryptes bato , Pampus chinensis , Liza parsia , Mugil cephalus , Hyporhamphus limbatus , and Tenualosa toil , since they all are consumed by locals of Bangladeshi population and reported six-times higher non-carcinogenic risk in children. Maurya et al 7 studied bioaccumulation and human health risk due to Zn, Pb, Cu, Cd, and Cr pollution in Cirrhinus mrigala , Cirrhinus reba , Catla catla , Labeo rohita , Crossocheilus latius , Clupisoma garua , and Mystus tengara collected from Ganga river basin.…”
Section: Introductionmentioning
confidence: 99%
“…To study bioaccumulation of multiple heavy metals in different tissues/species of fishes, MPI calculations is done to know the total metal load in a tissue. Recently, Ahmed et al (2019) reported accumulations of As, Pb, Cd, Cr, and Cu in six commercially important fishes. Among the heavy metals Cd, Pb, and Hg have been reported as highly toxic followed by Cu, Cr, Ni, Mn, and Zn ( Fernandes et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, death and decay of these plants require a huge quantity of oxygen which depletes oxygen level and such water exhibits higher values of biochemical oxygen demand (BOD) (Ferreira et al, 2017 [7]; Vigiak et al, 2019 [8]) that adversely affects the aquatic ecosystem. The excess and continuous presence of pollutants in the aquatic ecosystem makes their easy entry in the food chain and causes biomagnification which affects human health (Ahmed et al, 2019 [9]).…”
Section: Introductionmentioning
confidence: 99%